Meningkatkan Keaktifan Belajar melalui Penerapan Model Pembelajaran Team Games Tournament (TGT) Berbasis Pendekatan Deep Learning pada Murid SMAN 8 Muaro Jambi - Fitri Syabina; Ervan Johan Wicaksana; Lisa Rukmana (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This research was motivated by the low level of students’ learning activeness in class XI F1 at SMAN 8 Muaro Jambi. The observation results indicated that students tended to be passive, less participative, and easily bored during the learning process. Preliminary data showed that 59% of the students were categorized as having low learning activeness, while 41% were in the moderate category. This study aimed to improve students’ learning activeness through the implementation of the Team Games Tournament (TGT) learning model based on a deep learning approach. The method used in this study was Classroom Action Research (CAR), which was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of the study were 29 students of class XI F1. Data collection techniques included observation, questionnaires, and documentation, while the data were analyzed using descriptive quantitative analysis. The results showed a significant improvement in students’ learning activeness. In Cycle I, students’ learning activeness increased from 53% to 61% (moderate category). In Cycle II, it further increased to 70% and 79% (high category). Therefore, the implementation of the Team Games Tournament (TGT) learning model based on a deep learning approach proved to be effective in improving the learning activeness of students in class XI F1 at SMAN 8 Muaro Jambi